Review shows that implementing a nationwide protocol for congenital diaphragmatic hernia was a key factor in reducing mortality and morbidity. (7th February 2018) - Storme, L; Boubnova, J; Mur, S; Pognon, L; Sharma, D; Aubry, E; Sfeir, R; Vaast, P; Rakza, T; Benachi, A; ,
Abstract: The French Rare Disease Reference Center for congenital diaphragmatic hernia (CDH) was created in 2008, to implement a national protocol for foetuses and children with this serious condition. Neonatal mortality from CDH is 30‐40%, mainly due to pulmonary hypoplasia and persistent pulmonary hypertension, and half of those who live have high respiratory, nutritional and digestive morbidity. CDH management requires long‐term and specialised multidisciplinary care. It has been well established that a standardised management protocol improves the prognosis of children with CDH. Conclusion: Organising health care and implementing a nationwide French protocol were key factors for reducing mortality and morbidity from CDH. Abstract :